The African Peer Review Mechanism (APRM) as a tool to improve governance: experience in Ghana - Sven Grimm; Kristin Nawrath; Robert Roth; Simon Triebel; Britta Utz (Deutsches Institut für Entwicklungspolitik (DIE), 2009)
The quality of governance in Africa is particularly in discussion since the end of the Cold War. In 2002, African states created the African Peer Review Mechanism (APRM) with the declared goal to improve governance on the continent. Around half of Africa's states have agreed on conducting a self-assessment and discuss this with other heads of state and government. Ghana was the front runner in this process. As the first county to undergo an APRM, Ghana applied and also shaped the rules of the APRM. The aim of this study, which is the final report of a working group conducted in Ghana, is to look into the experience with the APRM in Ghana. Research was based on numerous interviews with stakeholders in the Ghanaian APRM, namely government officials, the national APRM secretariat, non-state actors and representatives of civil society. The study assesses the potential impact of the APRM on governance by considering the rigour or flexibility of its legal framework, the openness to participation in the self-assessment of Ghana, and the quality of the Ghanaian APRM report. It also takes a first look into whether recommendations of the report were implemented. From this analysis, the study assesses the APRM's potential for improving governance in Ghana and provides recommendations for APRM stakeholders and donors.
Keywords: 330